Peningkatan Daya Saing Produk E-KTP Reader AE01 PT. INTI melalui Pendekatan Nilai Pelanggan dan Inovasi Model Bisnis - darma, Darma Nugraha; Nila Armelia Windasari (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
The AE01 E-KTP Reader product developed by PT Industri Telekomunikasi Indonesia (PT INTI) faces competitive challenges in a market that is highly sensitive to price and customer value. This study aims to analyze customer value perceptions and formulate a business model innovation strategy to enhance the product’s competitiveness. A qualitative exploratory approach with a case study method was employed. Data were collected through in-depth interviews, internal document reviews, and literature studies, and analyzed using thematic analysis. The results indicate that functional value and cost are the dominant factors influencing customer purchasing decisions. Proposed business solutions include flexible financing schemes, product and service bundling, and improved technical documentation. The business model innovation strategy was developed using the Business Model Canvas (BMC) approach and structured into a three-month implementation plan. This research contributes to the development of value-based product strategies and business model innovation in state-owned technology enterprises.